The Effect of Zakat and Poverty on Economic Growth in West Java - Iman Supratman; Vemy Suci Asih (Indonesian Journal of Economics and Management, 2022)
Economic growth is one of the important aspects of how we can see the development of a region. Mature this consequence happening growth of the Covid - 19 pandemic Indonesia's economy experienced decline, as well as those affected in West Java. This paralyzes the productivity of economic activity which provokes the poverty rate to increase. In this case, as one of the alternative solutions for economic development instruments, zakat is here to provide incentives for economic growth. Top base that's study this done, also for look influence in a manner partial and simultaneous from poverty and zakat against growth economy in West Java in 2016-2020. Through method study descriptive with approach quantitative . Result of study showing that in a manner partial Zakat in kind Partial influential significant to growth economy with t count value 6.218353 > t table 1.978 or prob value > alpha 0.05. And poverty in a manner Partial influential to growth economy with -t count value -10.12971 < -t table -1.978 or mark probability 0.000 < alpha 0.5. As well as by simultaneous influential to growth economy with f count value 941.7948 > f table 3.065 or mark probability 0.000 < alpha 0.5.